Prioritizing Marketing Strategies for Market Competitiveness in a Small-Scale Tofu Enterprise: An Integrated SWOT–QSPM Case Study in Indonesia - Achmad Ridho Triagil (CV. SPDFHarmony, 2026)
Background: Traditional food microenterprises must often choose between protecting established product-based advantages and investing scarce resources in promotion, technology, or production growth. UD Daya Rasa, a small tofu enterprise in Kediri, Indonesia, experienced incomplete market absorption in part of its intermediary distribution channel while relying primarily on word-of-mouth promotion. Aims: This study identifies the enterprise’s internal and external strategic factors, determines its IE position, formulates marketing alternatives, prioritizes them through QSPM, and interprets the resulting order as a resource-capability sequencing problem. Methods: A descriptive single-case design used observation, interviews, enterprise records, and structured questionnaires collected in January–June 2023. The owner and an employee with at least ten years of experience provided IFAS–EFAS ratings, while one postgraduate academic expert provided QSPM attractiveness scores. Exact weights were reconstructed from the raw condition scores, and a one-factor ±10% weight-perturbation check was added without changing the original field data. Results: The exact calculations reproduced IFAS = 2.84 and EFAS = 2.85 after rounding, placing the enterprise in Cell V. Seven SWOT alternatives were retained. The originally reported QSPM ranked quality and distinctive-product protection first (TAS = 6.78) and use of diverse promotional media second (TAS = 6.42); two intermediate strategies tied at 5.94. The first-ranked strategy remained highest across all 40 deterministic ±10% weight-perturbation scenarios. Conclusion: The results support a cautious staged strategic implementation pathway in which the firm first protects and formalizes product quality, then amplifies that value through digital market communication, and scales production only after demand is verified. The study reframes SWOT–QSPM from a static ranking tool into a case-derived explanation of capability sequencing while explicitly acknowledging the limits of single-case and single-expert judgment.